Japanese Military Strategy in the Pacific War : Was Defeat Inevitable? - Wood, James B., 1946- (Rowman & Littlefield Publishers, Inc., 2007)
In this provocative history, James B. Wood challenges the received wisdom that Japan's defeat in the Pacific was historically inevitable. He argues instead that it was only when the Japanese military prematurely abandoned its original sound strategic plan--to secure the resources Japan needed and establish a viable defensible perimeter for the Empire--that the Allies were able to regain the initiative and lock Japanese forces into a war of attrition they were not prepared to fight. The book persuasively shows how the Japanese army and navy had both the opportunity and the capability to have fought a different and more successful war. If Japan had traveled that alternate military road, the outcome of the Pacific War could have differed significantly from that we know so well-and, perhaps a little too complacently, accept